PENGARUH PERSEDIAN DAN HUTANG JANGKA PANJANG TERHADAP LABA BERSIH PADA PT. ASTRA INTERNATIONAL, Tbk PADA TAHUN 2011-2020 - Linda Fitriyanti (Jurnal Manajemen FE-UB, 2023)
This study aims to examine the effect of Inventory and Long-Term Debt on Net Income at PT. Astra International Tbk for the 2010-2020 period. Based on the results of the analysis and discussion that has been carried out by the author and explained in CHAPTER IV, it can be concluded as follows: Based on the results of the F test (simultaneous) there is a negative and significant effect between inventory and long-term debt variables on net income with a probability value of 0. 610832. Based on the results of the t test (partial) the inventory variable has a negative and significant effect on net income with a probability value of 0.8728. Based on the results of the t test (partial) the long term debt variable has a negative and significant effect on net income with a probability value of 0.3437     Keywords: Inventories, Long-Term Debt, Net Income